The fox and the grapes: an Anglo-Irish perspective on conscientious objection to the supply of emergency hormonal contraception without prescription. Issue 10 (30th January 2013) - Gallagher, Cathal T; Holton, Alice; McDonald, Lisa J; Gallagher, Paul J
Abstract : Emergency hormonal contraception (EHC) has been available from pharmacies in the UK without prescription for 11 years. In the Republic of Ireland this service was made available in 2011. In both jurisdictions the respective regulators have included 'conscience clauses', which allow pharmacists to opt out of providing EHC on religious or moral grounds providing certain criteria are met. In effect, conscientious objectors must refer patients to other providers who are willing to supply these medicines. Inclusion of such clauses leads to a cycle of cognitive dissonance on behalf of both parties. Objectors convince themselves of the existence of a moral difference between supply of EHC and referral to another supplier, while the regulators must feign satisfaction that a form of regulation lacking universality will not lead to adverse consequences in the long term. We contend that whichever of these two parties truly believes in that which they purport to must act to end this unsatisfactory status quo. Either the regulators must compel all pharmacists to dispense emergency contraception to all suitable patients who request it, or a pharmacist must refuse either to supply EHC or to refer the patient to an alternative supplier and challenge any subsequent sanctions imposed by their regulator.